KONSERVASI DAN PEMANFAATAN LAHAN SEBAGAI UPAYA MENJAGA KELESTARIAN ALAM PERSPEKTIF HADIS NABI - Nurfauzi, Deril; Muthi'ah, Anisatun; Sakur, Lukman Zain M. (Jurnal Studi Hadis Nusantara, 2023)
This research is motivated by the increasing level of natural destructions. Many people think that the convenience of technology in this modern era will be a way to get convenience in life in this world. But in reality, there are many impacts of natural damage due to the rapid development of technology today. The universe basically has the most important role for living things. Because humans, plants, the universe and everything in it are creatures created by Allah SWT whose preservation must be protected. Departing from the background above, researchers are interested in researching more deeply about "the concept of protecting nature according to the hadith of the Prophet". So that it can be a solution in the midst of the level of natural destruction that has occurred in this era. This research uses descriptive qualitative methods. The author uses a form of library research, with data analysis techniques in the form of: descriptive analysis, takhrij, and ma'anil hadith. The research results show that the quantity of hadiths on preserving nature is included in the ahad hadith, namely gharib, because there is only one line of narrators, namely Abu Hurairah. As for the quality of the hadith to preserve nature, the transmitter is continuous (muttasil), there is no syadz, there is no illat, and the custom of each hadith narrated by Imam Bukhari and Imam Ahmad is the transmitter tsiqah, so that the hadith to preserve nature is included in the authentic hadith. Looking at the contextual meaning of this hadith, a moral idea can be drawn: â€don't let your land become neglected, because at least this can be beneficial not only for you, but also for the animals, plants or people around youâ€.